Examining reach, dose, and fidelity of the "Girls on the Move" after-school physical activity club: a process evaluation - Lorraine B. Robbins; Jiying Ling; Ebru Kilicarslan Toruner; Kelly A. Bourne; Karin A. Pfeiffer (BMC, 2016)
Abstract Background After-school programs represent a promising opportunity to assist adolescent girls' in attaining adequate physical activity. Although evaluating the process of intervention implementation is important for determining if an intervention was delivered and received as intended, comprehensive information about process evaluation methods and results are rarely reported. The purpose of this article was to evaluate the reach, dose, and fidelity of a 90-minute after-school physical activity club offered 3 days a week. The club is 1 of 3 components included in a 17-week intervention designed for 5th-8th grade girls, the majority of whom were of minority and/or low socioeconomic status. Methods A total of 24 schools (12 intervention; 12 control) and 56-67 girls per school (total N = 1519 girls) were included in the Girls on the Move group randomized controlled trial. At the beginning of each of 3 academic years (2012-2015), 8 schools per year were randomized to receive either the intervention (n = 4) or control condition (n = 4). To evaluate the club, data collected via surveys from girls, club coaches and managers, and process evaluators were analyzed. To evaluate the opportunity for physical activity provided by the coaches and managers, process evaluators used an observation tool based on the System for Observing Fitness Instruction Time and Academic Learning Time - Physical Education. Girls wore accelerometers every other week during the club time. Results Mean attendance was 41 % with the average attendance in year 3 being higher than rates for years 1 or 2. Mean moderate-to-vigorous physical activity time was 21.85 minutes measured via accelerometry and 21.81 minutes observed by process evaluators. Satisfaction with the intervention was high. For the most part, process evaluators perceived the club was delivered as planned and reflected constructs of the Health Promotion Model and Self-Determination Theory. Areas contributing to success included using incentives and offering a variety of activities. Issues negatively impacting implementation included managing behavioral problems, having limited space for moderate-to-vigorous physical activity, dealing with inclement weather, and getting coaches to actively participate in all physical activities with the girls. Conclusions This process evaluation provides important information to guide future school-based physical activity intervention delivery. Barriers to implementation have been identified. Ways to overcome them warrant consideration when designing physical activity interventions. Research is needed to test innovative approaches for enhancing attendance and increasing girls' moderate-to-vigorous physical activity in after-school programs. Trial registration ClinicalTrials.gov Identifier NCT01503333 . Registered 23 December, 2011.